NITROIMIDAZOLES VIII [I]. SYNTHESES, ANTIBACTERIAL AND ANTIFUNGAL ACTIVITIES OF 2-PYRIDYL-NITROIMIDAZOLES (Journal of Sciences, Islamic Republic of Iran)
Starting from 2-(2-pyridyl) imidazole a series of substituted imidazoles (2-5) were prepared. From the reaction of 2-(3-pyridyl) -4-(or 5) nitroimidazole (15) with dimethyl sulfate in alkaline medium 1-methyl-2-(3- pyridy1)-4-nitroimidazole (6,)w as prepared. Reaction of compound 15 with diazomethane gave I-methyl-2-(3-pyridy1)-5- nitroimidazol(e7 ) in addition to 6. The antibacterial and antifungal activities of compounds 5, 6, and 7 against a number of microorganisms were determined